The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1038/24634
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain communication regulating ligand binding by PPAR-γ

Abstract: Binding to receptors in the cell nucleus is crucial for the action of lipophilic hormones and ligands. PPAR-gamma (for peroxisome proliferator-activated receptor) is a nuclear hormone receptor that mediates adipocyte differentiation and modulates insulin sensitivity, cell proliferation and inflammatory processes. PPAR-gamma ligands have been implicated in the development of atherogenic foam cells and as potential cancer treatments. Transcriptional activity of PPAR-gamma is induced by binding diverse ligands, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
241
3
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(265 citation statements)
references
References 31 publications
(18 reference statements)
15
241
3
6
Order By: Relevance
“…We have shown that PPAR␣ activity is diminished by a post-transcriptional mechanism mediated by ERK-MAPK, confirming that signal transduction cascades linked to G-protein-coupled receptors can affect the activity of PPAR␣. Similarly, the related nuclear receptor, PPAR␥, is deactivated by ERK-mediated phosphorylation through a mechanism that reduces affinity for ligand (33)(34)(35)(36). Given these previous findings, the results shown here indicating that phosphorylation of PPAR␣ by p38 MAPK leads to activation of PPAR␣ function was surprising.…”
Section: P38 Mapk-mediated Activation Of Ppar␣ Maps To Phosphorylatiomentioning
confidence: 47%
See 1 more Smart Citation
“…We have shown that PPAR␣ activity is diminished by a post-transcriptional mechanism mediated by ERK-MAPK, confirming that signal transduction cascades linked to G-protein-coupled receptors can affect the activity of PPAR␣. Similarly, the related nuclear receptor, PPAR␥, is deactivated by ERK-mediated phosphorylation through a mechanism that reduces affinity for ligand (33)(34)(35)(36). Given these previous findings, the results shown here indicating that phosphorylation of PPAR␣ by p38 MAPK leads to activation of PPAR␣ function was surprising.…”
Section: P38 Mapk-mediated Activation Of Ppar␣ Maps To Phosphorylatiomentioning
confidence: 47%
“…p38 Activates PPAR␣A diverse array of molecular consequences have been attributed to nuclear receptor phosphorylation, including increased or decreased ligand-dependent and ligand-independent activation (reviewed in Ref. 37), enhanced recruitment of cofactors (38 -40), reduced affinity for ligand (33), increased or decreased capacity for DNA binding (reviewed in Ref. 37), enhanced or inhibited heterodimerization (41,42), and susceptibility to proteosomal degradation (43).…”
Section: P38 Mapk-mediated Activation Of Ppar␣ Maps To Phosphorylatiomentioning
confidence: 99%
“…Alternatively, moderate overexpression of PPAR␥ by itself may not be sufficient to change the phenotypic outcome. This possibility also is suggested by studies in cultured cells showing that overexpression of WT PPAR␥ has only a weak adipogenic effect in the absence of ligands (18,19).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, mitogen-activated protein kinase activation can strongly inhibit PPAR␥ activity, through direct phosphorylation of its amino-terminal A/B domain and a consequent negative intramolecular communication with the carboxylterminal ligand binding domain (Ref. 70 and references cited therein). These observations may then raise important questions on the specific role of PPAR␥ as immunoregulator and should lead to reconsidering its action in the context of concomitant pathways g of FasL-486Luc reporter and 4 g of pEQ176 CMV-␤-Gal expression vector as described in Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%